KONSERVASI KUPU-KUPU SEBAGAI SERANGGA PENYERBUK YANG PENTING DI TAMAN NASIONAL BANTIMURUNG-BULUSARAUNG - Sri Nur Aminah Ngatimin (Universitas Andi Djemma Palopo, 2019)
The purpose of study is to identify the species and frequency of butterfly visited on three types of flowers namely: Ixora paludosa, Hibiscus rosa-chinensis and Clerodendron japonicum. The information is very useful in the conservation effort of pollinator insects, especially butterflies that live around the Bantimurung-Bulusaraung National Park, Maros district, South Sulawesi, Indonesia. Research activities in the field trials were located in Simbang village (5 ° 01'23.2